PdFOAM: A PIC-DSMC code for near-Earth plasma-body interactions. (13th June 2017) - Capon, C.J.; Brown, M.; White, C.; Scanlon, T.; Boyce, R.R.
Highlights: The implementation and validation of the PIC-DSMC code, pdFOAM, is presented. Validation includes comparisons with MONACO and charging simulations. New insights into the role of dCPD on LEO objects are demonstrated. Bounded O+ ion jets are shown to cause a 4.4% increase in total dCPD. Bounded H+ ion jets are shown to cause a 23.7% reduction in total dCPD. Abstract: Understanding the interaction of the near-Earth space environment with orbiting bodies is critical, both from a design and scientific perspective. In Low Earth Orbit (LEO), the interaction between the Ionosphere and orbiting objects is well studied from a charging perspective. Not well understood is the effect of the Ionosphere on the motion of LEO objects i.e. ionospheric aerodynamics. This paper presents the implementation, validation, and verification of the hybrid electrostatic Particle-in-Cell (PIC) - Direct Simulation Monte Carlo (DSMC) code, pdFOAM, to study both the neutral and charged particle aerodynamics of LEO objects. The 2D aerodynamic interaction of a cylinder with a fixed uniform surface potential of − 50 V in mesothermal O + and H + plasmas representative of ionospheric conditions is investigated. New insights into the role of bounded ion jets and their effect on surface forces are presented. O + bounded ion jets are observed to cause a 4.4% increase in direct Charged Particle Drag (dCPD), while H + ion jets produce a net reduction in H + dCPD by 23.7% i.e. they cause a thrust force. As a result, this paper concludes the study of charged aerodynamics in LEO requires a self-consistent modelling tool, such as pdFOAM.